2013
DOI: 10.4028/www.scientific.net/amm.316-317.1133
|View full text |Cite
|
Sign up to set email alerts
|

Emulsification of Bio-Oil Heavy Fraction with Diesel by Mechanical and Ultrasonic Technologies

Abstract: In the present work, the emulsion fuels from bio-oil heavy fraction and 0# diesel were prepared by mechanical and ultrasound emulsification technologies. The relationship between stable time of emulsions and HLB value of emulsifier was investigated. Results indicated that lower mechanical stirring speeds and lower ultrasonic amplitudes lead to longer stable time of bio-oil heavy fraction emulsions. The stable time of emulsions reduced as HLB values increasing, and it reached a maximal value of 14 minutes under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Moreover, they found that the optimum hydrophilic-lipophilic balance, an important parameter for choosing an emulsifier, is directly proportional to the atomic O/C or H/C ratio, water content and inversely proportional to the high heating value of bio-oil. Other studies on the production of emulsions of bio-oil with diesel can be found elsewhere 252,253,256,[272][273][274][275] .…”
Section: Biofuels Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, they found that the optimum hydrophilic-lipophilic balance, an important parameter for choosing an emulsifier, is directly proportional to the atomic O/C or H/C ratio, water content and inversely proportional to the high heating value of bio-oil. Other studies on the production of emulsions of bio-oil with diesel can be found elsewhere 252,253,256,[272][273][274][275] .…”
Section: Biofuels Productionmentioning
confidence: 99%
“…Other studies on the production of emulsions of bio-oil with diesel can be found elsewhere. 251,252,254,255,273,274 7.2. Mixtures of Bio-oils with Other Fuels.…”
Section: Strategies For Purification and Separation Of Targeted Compo...mentioning
confidence: 99%
“…A surfactant added to NHO affects the separating effect between molybdenite and other sulfide minerals, resulting in excess impurities in the molybdenum concentrate. Several reports [22][23][24] found that ultrasonic treatment was also a successful method for improving the dispersibility of NHO in water. Ultrasonic treatment was found to produce small oil droplets and ensure homogenous distribution of oil droplets in water.…”
Section: Of 11mentioning
confidence: 99%